Abses Psoas Tuberkulosis - Sudirman, Taufik (Fakultas Kedokteran Universitas Pelita Harapan, 2016)
Psoas abscess is a rarely found abscess located in the iliopsoas compartment. It characterized by fever, back pain, and limitation of hip movements. Psoas abscess is hard to diagnose due to only 30% of classic symptoms and signs are found. In this study we discussed tuberculous psoas abscess in patient 26 years old male. Anamnesis, physical examination, and supporting medical tests were done to diagnose tuberculous psoas abscess. Therefore we performed abscess incision and drainage, followed by continuous tuberculous therapy.Keywords: tuberculous psoas abscess